Demystifying modern slavery - Broad, Rosemary; Gadd, David 1975- (Routledge, 2023)
Introduction -- Demystifying Modern Slavery -- Evil Slave Masters as Political Folk Devils -- People Smuggling -- Organised Criminals? -- Sham Marriage -- Domestic Servitude -- Labour Exploitation -- Adult Sex Trafficking -- Child Sexual Exploitation -- Conclusion.
Keywords: Sklaverei; Ausbeutung; Menschenhandel; Slavery / History / 21st century; Human trafficking / History / 21st century; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Emigration & Immigration